Disciplinary Progress in International Relations: the Definition of International Actor in the Study of Paradiplomacy - Oddone, Nahuel (2019)
The commemoration of the foundation of International Relations as a scientific discipline, finds the analysis of International Relations in a stage of review and reinterpretation of its trajectory. The ongoing assessment addresses issues such as epistemology, theories, debates, and research agendas focusing on the influence of contexts and stakeholders in the development of the discipline, including local and regional governments. This article alludes to texts and contexts appraising the way in which the theory of International Relations has analyzed subnational international performance. In particular, the way in which such activities have entered this field of study since its founding stage, paying attention to the revision of the category of international actor in the study of paradiplomacy.